Generic Modals in Mandarin - Shih, Chun-Hung (Proceedings of the Amsterdam Colloquium, 2024)
Generics express events occurring with some regularity or general stable properties (Krifka et al. 1995). While generics are mostly realized in the present tense without a dedicated morpheme in English, the morpheme hui is used in Mandarin in certain cases, which has been claimed to be a generic modal and related to its epistemic/future and ability usages (Chang 2001, Tsai 2015, Wu 2020). However, this generic modal hui is not present in all generic sentences. With an investigation of the distribution and licensing of hui, this paper shows (1) that this morpheme occurs with episodic/stage-level predicates but not stative/individual level ones, and (2) that adverbs, negators, and polarity operators can license this morpheme in stative/individual-level predicates (see also Wu 2020). This paper claims that Mandarin has two generic operators, providing independent evidence for Chierchia’s (1995) theory of a distinction between two generic operators. One type is realized by hui and situated in Spec,AspP with restrictions on the conditions under which the relevant event typically occurs, while the other is realized covertly and situated in Spec,VP with a restriction on the location where the eventuality holds. This paper further proposes a stacking of two generic operators, based on the empirical facts in Mandarin.